Imperfect ownership in common property: An analysis of islamic law and judicial policy - Mowafg Abrahem Masuwd; Sarkanto; Mohammad Abdul Munjid; Amel Grasine Farona (Yayasan Azhar Amanaa Yogyakarta, 2025)
This paper aims to examine the imperfect status of ownership in the distribution of common property (gono-gini) from the perspective of Islamic law and positive Indonesian law, especially in the context of assets that are still pledged or have not been paid off. This problem becomes particularly relevant considering the number of married couples who acquire assets in the form of credit during their marriage period. This study employs a normative juridical method with a comparative approach, analyzing the norms of Islamic law, the Compilation of Islamic Law (KHI), and the Supreme Court Circular Letter (SEMA) No. 3 of 2018, and comparing them with judicial practices in religious courts. The results show that positive legal approaches that emphasize formal ownership tend to overlook each party's actual contribution in acquiring property, thereby risking the creation of injustice. On the contrary, the principle of substantive justice in Islamic law provides room for recognizing real contributions through conditional apportionment mechanisms and proportional assessments that are more adaptable to the socio-economic dynamics of households.